Identifying Personal and Contextual Factors that Contribute to Attrition Rates for Texas Public School Teachers - Sass, Daniel Allen; Flores, Belinda Bustos; Claeys, Lorena; Pérez, Bertha (Education Policy Analysis Archives, 2012)
Teacher attrition is a significant problem facing schools, with a large percentage of teachers leaving the profession within their first few years. Given the need to retain high-quality teachers, research is needed to identify those teachers with higher retention rates. Using survival analyses and a large state dataset, researchers examined teacher data to identify those teacher and school variables associated with attrition. Unique to this study was the investigation of testing era (basic competency vs. higher standards based), school districts’ yearly ratings based on state-mandated testing, and charter school status. Analyses revealed that teacher attrition was greater during the high stakes-testing era, at low-performing schools, and for charter schools; however, beginning teacher age, gender, and school level moderated several attrition rates. Implications for public policy are discussed.